2016
DOI: 10.1194/jlr.d066472
|View full text |Cite
|
Sign up to set email alerts
|

Following the flux of long-chain bases through the sphingolipid pathway in vivo using mass spectrometry

Abstract: This article is available online at http://www.jlr.org sphingolipids, and plants can make of three classes of sphingolipids (3-6).Sphingolipids and their biosynthetic precursors, longchain base (LCB) and ceramide, have structural as well as signal functions; their synthesis and turnover thus must be precisely controlled (7). The rate-limiting step of the pathway is under control of serine palmitoyltransferase (SPT), an endoplasmic reticulum (ER)-localized protein complex that catalyzes the condensation of palm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…1 A). It has previously been shown that cells lacking either of these synthases have reduced levels of ceramides (Schorling et al, 2001;Rego et al, 2012;Martínez-Montañés and Schneiter, 2016). In contrast, cells lacking Orm1p, Orm2p, and Lcb4p, which phosphorylates sphingosine and other LCBs, remain hypersensitive to tunicamycin ( Fig.…”
Section: Nvj2p Prevents the Toxic Accumulation Of Ceramidesmentioning
confidence: 93%
“…1 A). It has previously been shown that cells lacking either of these synthases have reduced levels of ceramides (Schorling et al, 2001;Rego et al, 2012;Martínez-Montañés and Schneiter, 2016). In contrast, cells lacking Orm1p, Orm2p, and Lcb4p, which phosphorylates sphingosine and other LCBs, remain hypersensitive to tunicamycin ( Fig.…”
Section: Nvj2p Prevents the Toxic Accumulation Of Ceramidesmentioning
confidence: 93%
“…Moreover, assays that utilize thin layer chromatography for the detection of the labeled lipids are unable to discriminate the variations in the Nacyl chain length, which can play a role in sphingolipid biology [22][23][24]. One approach to dissecting cellular pools of lipids is to utilize a label such as an unnatural 17 carbon sphingoid base for flux analysis monitored by LC/MS/MS [25,26]. Assays of this nature have been utilized to assess CerS and SK activities measuring the conversion of d17sphingosine (d17Sph) into d17ceramide (d17Cer) or d17sphingosine-1-phosphate (d17S-1-P), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas wild-type cells respond in a dose-dependent manner to the addition of C17-PHS, Orm mutant cells display a reduction in ceramide and IPC synthesis if higher concentrations of C17-PHS are supplied [57].…”
Section: Odd-chain Length Long-chain Basesmentioning
confidence: 98%
“…In vitro assays to monitor sphingosine kinase or ceramide synthase activities by using non-naturally occurring C17-sphingosine or C17-DHS as substrates followed by product detection by mass spectrometry have been described previously [56]. More recently, administration of C17-PHS to living yeast cells was employed to monitor ceramide synthase and IPC production in vivo and yielded insights into the complex regulation of the pathway [57].…”
Section: Odd-chain Length Long-chain Basesmentioning
confidence: 99%